2020
DOI: 10.1097/inf.0000000000002902
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, Perinatal and Neonatal Outcomes With COVID-19: A Multicenter Study of 242 Pregnancies and Their 248 Infant Newborns During Their First Month of Life

Abstract: Background: Our aim was to describe the clinical features of mothers with coronavirus disease 2019 (COVID-19) infection during gestation or delivery, and the potential vertical transmission. We also wish to evaluate the possible horizontal transmission after hospital discharge, by means of a follow-up of all the newborns included at 1 month of age. Methods: This multicenter descriptive study involved 16 Spanish hospitals. We reviewed the medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 42 publications
1
30
1
1
Order By: Relevance
“…Even in the presence of placental injury, the neonatal outcomes have been consistently been good in COVID-19 pregnancies. In 242 pregnancies and their 248 newborns, risk of premature delivery was increased but none of the babies died and no vertical or horizontal transmission was documented [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the presence of placental injury, the neonatal outcomes have been consistently been good in COVID-19 pregnancies. In 242 pregnancies and their 248 newborns, risk of premature delivery was increased but none of the babies died and no vertical or horizontal transmission was documented [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While preterm deliveries occur more often in women with suspected or confirmed SARS-CoV-2 infection, no increase in stillbirth or early neonatal death was found (Mullins et al 2021). Prospective and retrospective studies showed that pregnant women infected with SARS-CoV-2 are at increased risk of adverse events, including higher rates of cesarean section and increased post-partum complications (Woodworth et al 2020; Prabhu et al 2020; Marín Gabriel et al 2020). While vertical transmission of SARS-CoV-2 from mother to fetus has been reported in a few cases (Hecht et al 2020a; Vivanti et al 2020; Taglauer et al 2020; Facchetti et al 2020; Woodworth et al 2020; Hecht et al 2020b; Alamar et al 2020), most studies did not detect viral transmission (Penfield et al 2020; Baergen and Heller 2020; Prabhu et al 2020; Salvatore et al 2020; Edlow et al 2020; Schwartz 2020; Della Gatta et al 2020; Kimberlin and Stagno 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that peripartum-postnatal transmission is rare(American Academy of Pediatrics, 2020cDumitriu et al, 2020;Salvatore et al, 2020) or uncommon(Maraschini, Corsi, Salvatore, Donati, & It, 2020;Marin Gabriel et al, 2020;Patil et al, 2020;Walker et al, 2020), and even larger studies show serious neonatal outcomes are rare (American Academy of Pediatrics, 2020e;MarinGabriel et al, 2020). The rate of infection is no greater when the newborn is delivered vaginally, breastfed or kept together with the mother (American Academy of Pediatrics, 2020c; Centers for Disease Control and Prevention, 2020;Dumitriu et al, 2020;Patil et al, 2020;Walker et al, 2020).Moreover, older infants and young children who do contract COVID-19 seem to get mild or no symptoms and rarely get sick(American Academy of Pediatrics, 2020b;Bixler et al, 2020;Hoang et al, 2020;Kim et al, 2020).…”
mentioning
confidence: 99%